Exact solitary wave solution for the fractional and classical GEW-Burgers equations: an application of Kudryashov method. Issue 3 (4th May 2018) - Nuruddeen, R. I.; Nass, Aminu M.
ABSTRACT: The fractional partial differential equations have wide applications in science and engineering. In this paper, the Kudryashov techniques were utilized to obtain an exact solution of both fractional generalized equal width (GEW)-Burgers and classical GEW-Burgers equations. The general analytical solutions of the two partial differential equations are constructed for n >1. The graphical representation of the solutions is given in comparison with some previous results in the literature. The advantages and disadvantages of the method were listed.